2019
DOI: 10.1177/0972150919832770
|View full text |Cite
|
Sign up to set email alerts
|

Does Inward FDI Lead to Export Performance in India? An Empirical Investigation

Abstract: This article investigates whether or not inward foreign direct investment (FDI) leads to export performance in India over the time period 1980—2017. We use Augmented Dickey–Fuller and Phillip–Perron unit root test to check the stationarity, and it confirms that all the variables are stationary at first differences I(1). The auto regressive distributed lag (ARDL)-bound testing co-integration approach confirms that there is no valid long-run relationship between considered variables. Results indicate the insigni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…Domestic determinants such as sound macroeconomic policies, good governance, human capital, political stability and national savings are crucial for economic growth (Narayan, 2004;Romer, 1986;Roubini and Wachtel, 1999;Solow, 1956). However, in recent times, factors outside the domestic economy, namely, exports, remittances, foreign direct investment (FDI) and FIIs have also become key enablers of economic growth (Azman-Saini et al, 2010;Barajas et al, 2009;Chen and Jayaraman, 2016;Mohanty and Sethi, 2019), particularly for the developing countries like those situated in the South Asian region, which are in need of foreign capital as well as foreign technology. The sustainable growth of an economy is fundamental because a healthy, growing economy has a great potential to reduce unemployment and alleviate poverty which is readily needed in the countries in the South Asian region.…”
Section: Introductionmentioning
confidence: 99%
“…Domestic determinants such as sound macroeconomic policies, good governance, human capital, political stability and national savings are crucial for economic growth (Narayan, 2004;Romer, 1986;Roubini and Wachtel, 1999;Solow, 1956). However, in recent times, factors outside the domestic economy, namely, exports, remittances, foreign direct investment (FDI) and FIIs have also become key enablers of economic growth (Azman-Saini et al, 2010;Barajas et al, 2009;Chen and Jayaraman, 2016;Mohanty and Sethi, 2019), particularly for the developing countries like those situated in the South Asian region, which are in need of foreign capital as well as foreign technology. The sustainable growth of an economy is fundamental because a healthy, growing economy has a great potential to reduce unemployment and alleviate poverty which is readily needed in the countries in the South Asian region.…”
Section: Introductionmentioning
confidence: 99%
“…The overall crowd-in effect can be explained in the literature. Foreign direct investment is known to promote knowledge, technology transfer, exports expansion, product and process innovation (Djulius, 2017;Jawaid et al, 2016;Jin et al, 2019;Mohanty & Sethi, 2019;Schneider & Wacker, 2020;Viglioni & Calegario, 2020). Whilst employees could share knowledge on the job, labour mobility within the food manufacturing sector (from MNEs to domestic firms), would also lead to knowledge diffusion.…”
Section: Discussion Of Estimationsmentioning
confidence: 99%
“…The pessimistic school of thought may not rule out completely attracting inward FDI but is of the opinion that it does not in any way improve international trade. Using ARDL technique, Mohanty and Sethi (2019) found that there is a negative and significant impact of FDI on real exports in long term but positive in the short term.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%